Application Contingency Analysis of An IEEE 30 Bus System Using Matpower - Abedin T.; Aini N.; Sivanyanam D.D.; Pasupuleti J. (Institute of Physics, 2023)
Electric equipment protection; Electric load flow; Electric power system protection; MATLAB; Brach outage; Bus systems; Component failures; Contingency analysis; Generator outage; Newton-raphson; Per unit; Performance indices; Power system protection; Severity; Outages